Impact of isolation method on doubling time and the quality of chondrocyte and osteoblast differentiated from murine dental pulp stem cells - Megat Abdul Wahab,Rohaya; Mohamed Rozali,Nur Akmal; Senafi,Sahidan; Zainol Abidin,Intan Zarina; Zainal Ariffin,Zaidah; Zainal Ariffin,Shahrul Hisham (PeerJ, 2017)
Background Stem cells are normally isolated from dental pulps using the enzymatic digestion or the outgrowth method. However, the effects of the isolation method on the quality of the isolated stem cells are not studied in detail in murine models. The aim of this study was to compare the matrices secreted by osteoblast and chondrocytes differentiated from dental pulp stem cells isolated through different means. Method DPSC from murine incisors were isolated through either the outgrowth (DPSC-OG) or the enzymatic digestion (DPSC-ED) method. Cells at passage 4 were used in this study. The cells were characterized through morphology and expression of cell surface markers. The cells’ doubling time when cultured using different seeding densities was calculated and analyzed using one-way ANOVA and Tukey’s multiple comparison post-test. The ability of cells to differentiate to chondrocyte and osteoblast was evaluated through staining and analysis on the matrices secreted. Results Gene expression analysis showed that DPSC-OG and DPSC-ED expressed dental pulp mesenchymal stem cell markers, but not hematopoietic stem cell markers. The least number of cells that could have been used to culture DPSC-OG and DPSC-ED with the shortest doubling time was 5 × 102 cells/cm2 (11.49 ± 2.16 h) and 1 × 102 cells/cm2 (10.55 h ± 0.50), respectively. Chondrocytes differentiated from DPSC-ED produced  2 times more proteoglycan and at a faster rate than DPSC-OG. FTIR revealed that DPSC-ED differentiated into osteoblast also secreted matrix, which more resembled a calvaria. Discussion Isolation approaches might have influenced the cell populations obtained. This, in turn, resulted in cells with different proliferation and differentiation capability. While both DPSC-OG and DPSC-ED expressed mesenchymal stem cell markers, the percentage of cells carrying each marker might have differed between the two methods. Regardless, enzymatic digestion clearly yielded cells with better characteristics than outgrowth.
Keywords: Dental pulp; Enzymatic digestion; Outgrowth; Osteoblast; Stem cell; Chondrocyte